Redox Tuning in Photosystem II. (February 2017) - Allen, John F.; Nield, Jon
Abstract : In photosynthesis, oxygen is liberated from water, not from CO2 ; however, this model has been silent on why photosynthesis requires bicarbonate. Rutherford and colleagues solve this problem elegantly: bicarbonate tunes water-oxidising photosystem II to make onward electron transfer efficient; an absence of bicarbonate retunes, redirects, and safely shuts down energy flow.